Topographically guided hierarchical mineralization. (June 2021) - Deng, X.; Hasan, A.; Elsharkawy, S.; Tejeda-Montes, E.; Tarakina, N.V.; Greco, G.; Nikulina, E.; Stormonth-Darling, J.M.; Convery, N.; Rodriguez-Cabello, J.C.; Boyde, A.; Gadegaard, N.; et al.
Abstract: Material platforms based on interaction between organic and inorganic phases offer enormous potential to develop materials that can recreate the structural and functional properties of biological systems. However, the capability of organic-mediated mineralizing strategies to guide mineralization with spatial control remains a major limitation. Here, we report on the integration of a protein-based mineralizing matrix with surface topographies to grow spatially guided mineralized structures. We reveal how well-defined geometrical spaces defined within the organic matrix by the surface topographies can trigger subtle changes in single nanocrystal co-alignment, which are then translated to drastic changes in mineralization at the microscale and macroscale. Furthermore, through systematic modifications of the surface topographies, we demonstrate the possibility of selectively guiding the growth of hierarchically mineralized structures. We foresee that the capacity to direct the anisotropic growth of such structures would have important implications in the design of biomineralizing synthetic materials to repair or regenerate hard tissues. Graphical abstract: Image 1